STORMWATER EVALUATION AND MANAGEMENT IN THE URBAN WATERSHED OF UYO METROPOLIS, NIGERIA, EMPLOYING GIS SIMULATION - NSIEGBE, Dickson Kinikawo; ABALI, Temple Probyne; IDEKI, Oye; NKII, Lucky Baripara (American Journals Publishing, 2022)
In several Nigerian cities, storm water management is a significant challenge. Local flooding is common in urban settings because storm water is channeled along streets because runoff may not be able to escape the environment and create floods. As a result, severe rains are related with floods and other disasters in Nigerian cities. Storm water harvesting from point sources, water management, and purification (treatment) are sustainable techniques that can make metropolitan environments self-sufficient in terms of water supplies. The study aims to evaluate stormwater generation and management, which encompasses hard and soft engineering projects involving the construction, operation, and maintenance of dams, artificial levees, and other structures that are comparable like dams, artificial levees, and channel straightening are examples of construction, operation, and maintenance approaches. To achieve the study's goal, the researchers used a correlational research design in which data was analyzed using hydrological modeling techniques and GIS. As a result, a model was created to depict stormwater generation by balancing and overlaying DEM data in a pairwise comparison of stormwater flow against rainfall intensity and topography pattern using multi criteria evaluation. The investigation and findings demonstrate that the simulated sub catchment runoff in Uyo metropolis is higher than expected, whereby four catchments were used for the runoff generation, it is vividly shown that the total precipitation in each of the sub catchments is similar which was 1.57 inches while the total infiltration read 0.79 inches, the total runoff was 0.74 inches and 0.08x 106 gallon. The study concludes that better city planning is required to manage the stormwater problem through various engineering projects, based on the findings. The following are some suggestions: To achieve sustainable urban growth and development, implement the uyo City Master Plan to guide, monitor, control, and manage the areas designated as urban lands. Storm Water Management Framework should be prepared for the city having Storm Water Master Plan to control, manage, and monitor storm water as a state policy and urgency – Model for Urban Stormwater Improvement Conceptualisation (MUSIC), 2002 Approach, Structural (engineering methods) and Non-structural (regulations and standards) Storm Water Management approaches should be employed to control and manage flooding challenges in the city.
Keywords: GIS; Stormwater; Modelling